2013
DOI: 10.1128/aem.02920-12
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and Heterogeneity of Escherichia coli MC1000 Growing in Complex Environments

Abstract: bIn a study aiming to assess bacterial evolution in complex growth media, we evaluated the long-term adaptive response of Escherichia coli MC1000 in Luria-Bertani (LB) medium. Seven parallel populations were founded and followed over 150 days in sequential batch cultures under three different oxygen conditions (defined environments), and 19 evolved forms were isolated. The emergence of forms with enhanced fitness was evident in competition experiments of all evolved forms versus the ancestral strain. The evolv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(44 citation statements)
references
References 56 publications
3
39
1
Order By: Relevance
“…Indeed, we observed a fitness improvement much greater than that which has been seen in previous long-term evolution experiments at pH 5.3 (31). Our experiment was performed in a complex medium, LBK mal , which broadened the range of possible metabolic responses and, hence, targets of selection to the acidic conditions (9,27). Evolved populations showed both a significantly higher endpoint culture density ( Fig.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Indeed, we observed a fitness improvement much greater than that which has been seen in previous long-term evolution experiments at pH 5.3 (31). Our experiment was performed in a complex medium, LBK mal , which broadened the range of possible metabolic responses and, hence, targets of selection to the acidic conditions (9,27). Evolved populations showed both a significantly higher endpoint culture density ( Fig.…”
Section: Discussionmentioning
confidence: 52%
“…A protocol based on successful evolution protocols described in the literature (22,25,27) was devised for experimental evolution of E. coli growth at external pH values below 5. Twentyfour populations were established from the same parental freezer stock of strain W3110.…”
Section: Experimental Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of unexplored (vacant) niches in the aforementioned habitats may thus constitute a key driver of the rapid emergence of novel bacterial types in initially homogeneous populations (Rainey and Travisano, ; MacLean et al ., ; Puentes‐Téllez et al ., ), in which frequency‐dependent selection may be involved (Friesen et al ., ; Tyerman et al ., ). One may consider complex environments with nutrient mixtures to offer spatial ‘structure’ with fine‐scale variation (Kassen, ).…”
Section: Introductionmentioning
confidence: 99%
“…Two distinct metabolic types were identified after analysis of multiple colonies from the evolved population. Initial studies of these revealed that colony morphology correlated with some distinct genotypes and phenotypes (Puentes‐Téllez et al ., 2013; 2014). Here, we further explore the ecological nature of selected divergent types that apparently maintained a coexisting interaction.…”
Section: Introductionmentioning
confidence: 99%